Impact of liquidity and business efficiency on the profitability of industrial companies of the superintendency of the stock market - Altamirano Mocarro, Iris Maribel; Delgado Rubio, Kiara Nicolle; Obregón Vara, Flor Elizabeth; Pintado Castillo, Cesar Agusto (LACCEI, 2025)
From 2014 to 2024, Peruvian industrial companies under the supervision of the Superintendency of the Securities Market (SMV) faced financial challenges, including fluctuations in liquidity and operational efficiency. This study examined the impact of these factors on business profitability using return on assets (ROA) and return on equity (ROE) as key performance indicators. A quantitative approach with a non-experimental, correlational, and retrospective design was employed. The sample consisted of four industrial companies selected using non-probability convenience sampling. All of these companies reported weak financial results during the study period. The findings suggest that although there was a positive relationship between liquidity and profitability, it was not statistically significant (ρ = 0.256; p = 0.102). This indicates that liquidity alone does not determine economic performance. In contrast, operational efficiency showed a strong, statistically significant positive correlation with profitability (ρ = 0.960; p < 0.01), demonstrating that effective resource management directly contributes to profit generation. The joint analysis revealed significant heterogeneity among the companies, reflecting disparities in financial and operational practices. It can be concluded that, in addition to maintaining adequate Liquidity is also a critical factor in enhancing profitability. This is essential for ensuring financial sustainability in the industrial sector.